Associated and adjoint koszul connection - 311576 Niki Anis Ab. Karim; Tahir Ahmad, Supervisor; Fakulti Sains (2009)
Supervisor :Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2009